Mosquito fauna inhabiting water bodies in the urban environment of Córdoba city, Argentina, following a St. Louis encephalitis outbreak - Pires, Diego Ariel (2010)
An understanding of urban aquatic environments as mosquito larval habitats is necessary to prioritize sites for surveillance and control of arbovirus vectors in urban areas. Natural and artificial water bodies at ground level that may be larval mosquito habitats in Córdoba city, Argentina were surveyed. Data on the characteristics of aquatic sites and the presence and abundance of mosquito larvae and pupae were collected in the summer of 2006, coinciding with the first report of human WNV and following an outbreak of St. Louis encephalitis in 2005. Eight species in the genera Aedes, Culex, and Mansonia were identified. At 64.2% (34 of 53) of the sites, only one species was collected, while 3.8% (2 of 53) had three associated species, the highest richness found per site. Culex quinquefasciatus represented over 99% (out of 32,729) of the specimens. It was also the most widely distributed and detected under diverse habitat conditions. Although puddles and semi-permanent pools harbored a greater number of species, drainages and channels may be more relevant as risk factors from an epidemiological point of view because they showed the highest larval densities, mainly of Cx. quinquefasciatus (vector of SLE and WNV). Also, higher densities of this species were associated with stormwater runoff and sewage water, thus water management systems should be targeted and closely monitored for mosquito control purposes.